Research and Application Progress of Special Acupuncture Combined with Three-Step Analgesia Method in the Treatment of Cancer Pain - Zhou, Jin; Wang, Yuanchun; Wang, Xiaoxue (Journal of Contemporary Medical Practice, 2026)
Cancer pain is one of the most common symptoms experienced by cancer patients, significantly impacting their quality of life. Currently, Western medicine employs the three-step ladder approach as the primary treatment for cancer pain. However, the accompanying adverse reactions such as nausea and vomiting limit its clinical application to some extent and affect the ultimate efficacy of cancer pain management. Specialized acupuncture techniques, developed through innovation based on traditional acupuncture, offer advantages such as rapid onset and high efficacy in cancer pain management. In recent years, they have demonstrated an increasingly significant role in the comprehensive management of cancer pain. This review aims to systematically summarize the research progress and current applications of specialized acupuncture combined with the three-step analgesic approach in cancer pain treatment, with the goal of providing reference for clinical application and cancer pain management.